Exophthalmos: A Forgotten Clinical Sign of Cushing's Syndrome. (10th March 2013) - Giugni, Aldo Schenone; Mani, Shylaja; Kannan, Subramanian; Hatipoglu, Betul
Abstract : Exophthalmos is typically associated with Graves' ophthalmopathy. Although originally described by Harvey Cushing, exophthalmos is an underappreciated sign of Cushing's syndrome. We present a case of a 38-year-old female who presented with severe bilateral proptosis and was subsequently diagnosed with Cushings disease. We discuss the possible mechanisms causing exophthalmos in patients with either endogenous or exogenous hypercortisolemia.